The Development of Formal Islamic Educational Institutions in Salatiga in 1932-1998 - Candra, Lutfiana; Kusumaningtyas, Juwita Artanti (Islah: Journal of Islamic Literature and History, 2023)
Islamic Education Institution refers to a place or organization conducting Islamic Education, with a clear structure and responsibility for the implementation of Islamic Education. Islamic education in Salatiga began in 1932. During the Independence period, the education system improved. Since then, formal Islamic education in Salatiga underwent a transformation from the initial marginalization to the proliferation of Islamic educational institutions in all areas of Salatiga. Therefore, this study aims to examine the History and Development of Formal Islamic Education Institutions in Salatiga City from 1932 to 1998. This research applies the historical research method. The stages within the historical research method are (1) Heuristics or data collection, (2) Verification or source criticism, (3) Interpretation or analysis of historical facts, and (4) Historiography or historical writing. The approach in this research is the theory of social change using the concept of formal Islamic Education Institutions and the concept of Islamic education. The results of this study indicate the following: (1) Salatiga is a city of colonial growth and development, from a village to an important city for the colonial authorities. Moreover, it won the De Schoonstestad Van Midden Java or the Most Beautiful City in Central Java award; (2) The emergence of education in Salatiga cannot be separated from the existence of the Dutch government. The Ethical Policy promoted the emergence of educated people in Salatiga; (3) The growth of Dutch educational institutions was inversely compared to formal Islamic educational institutions in Salatiga. It encouraged Muslim scholars to establish formal Islamic educational institutions in Salatiga. HIS Muhammadiyah marks the beginning of formal Islamic educational institutions in Salatiga. The growth and the development of Islamic educational institutions in Salatiga cannot be separated from the government's policy and the initiative of Muslims to build educational systems and institutions appropriate to the times, from primary to tertiary levels.